Healing of Benign Gastric and Prepyloric Ulcers: A Prospective, Endoscopy-Controlled, Randomized, Double-Blind, Canadian Multicentre Study of Omeprazole 20 and 40 mg Daily and Rantidine 150 mg Twice a Day - Pierre Paré; Robert J Bailey; André P Archambault; Henri Navert; C Noel Williams; ABR Thomson; Denis Levesque; Alain Farley (Canadian Journal of Gastroenterology)
A double-blind, randomized study was conducted in 118 patients with benign gastric or prepyloric ulcers to compare the efficacy of omeprazole 20 or 40 mg daily with ranitidine 150 mg twice daily. The healing rates at four weeks were 67, 79 and 54% and at eight weeks increased to 90, 97 and 71 % for the omeprazole 20 and 40 mg groups and the ranitidine group, respectively (P< 0.03 for the differences between each of the omeprazole groups and the ranitidine group at eight weeks). Multivariate analysis showed influence on healing rate for ulcer size but not for smoking status, sex or ulcer site. Symptomatic relief was excellent and similar in the three groups. Ulcer recurrence during the six month follow-up off treatment after initial ulcer healing did not differ between the three groups. No serious adverse events could be attributed to the drugs. The authors conclude that treatment with omeprazole 20 or 40 mg daily for a period of four to eight weeks is safe and significantly more effective in ulcer healing than a standard dose of ranitidine.